ICARE Learning Model in Improving the Students Writing Ability - Ammang Latifa; Rafi'ah Nur; Ahmad Rizal (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2020)
This research explored the use of the ICARE Model to studying the writing ability at the Senior high school in Parepare. ICARE includes five essential elements of a good learning experience, can be applied to children, teenagers, and parents, namely Introduction, Connection, Application, Reflection, and Extension. This research involved a population from Senior high school in Parepare in the academic year 2015/2016. The students consist of two classes, an experimental class, and a control class. Each class consists of 36 students. This research utilized a cluster random sampling technique to select the sample. The instrument used in this research is the writing test. The data were analyzed by using t-test. The research reveals that there was a significant increase in students writing ability. This finding indicates that the mean score of the post-test of the experimental group is getting much better than the control class. It meant that using ICARE developed the students' ability in writing, and the writing component increased the highest is in the vocabulary aspect.